IMPACT OF EMPLOYEE JOB SATISFACTION ON EMPLOYEE PERFORMANCE - Asraa Sindi; Uzma Javed (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
With the changing workforce, the attitudes of employees are also changing over time, as there has been a major shift in the way people used to work earlier than the current one. The attitude of employees plays an important role in the efficient functioning of the organization. It is divided into many aspects, one of which is job satisfaction. When employees are satisfied with their work, they tend to perform well in the long run. This study has analyzed the impact of employee job satisfaction on employee performance at Jeddah, Saudi Arabia. The study was carried out based on quantitative method, comprising of 103 employees from the private sector. Data collection was done using survey method. The findings concluded that there is a positive relationship between employee satisfaction and employee performance, thereby improving the performance of the organization. The majority of employees are highly satisfied with the different factors at work and therefore their performance is also improved.